IMPROVING INCLUSIVITY IN ELEMENTARY SCHOOLS THROUGH STRUCTURED MULTICULTURAL EDUCATION MODELS AND COMPREHENSIVE TEACHER TRAINING - Lestari, Nila; Maksum, Arifin; Nurhasanah, Nina (Universitas Negeri Surabaya, 2025)
Elementary schools, inclusivity, multicultural education, socPhenomenon/Issue: As global societies become increasingly diverse, elementary education faces the challenge of fostering inclusivity and cultural understanding among young students. This study explores the effectiveness of implementing structured multicultural education models and the role of teacher training in enhancing these educational practices. Purpose: The purpose of this research is to assess how multicultural education impacts students' social attitudes and reduces biases in elementary schools, and to examine how teacher preparedness contributes to the success of these programs. Novelty: This study contributes novel insights by highlighting the dual importance of structured curriculum and comprehensive teacher training in successfully embedding multicultural education at the elementary level. Unlike previous studies, this research emphasizes the combined impact of curriculum design and teacher readiness on fostering inclusive social behaviors. Research Methods: Using a qualitative approach, this study gathered data from classroom observations, in-depth teacher interviews, and document analysis across diverse elementary school settings. Results: Findings reveal that multicultural education models positively impact students' social attitudes, enhancing empathy and tolerance. Furthermore, well-trained teachers are better equipped to deliver multicultural education, significantly amplifying its benefits. Research Contributions: This research underscores the importance of integrated teacher training and multicultural curricula, providing a framework for future policies aimed at creating inclusive educational environments. The study calls for broader implementation of these practices and further research on long-term impacts across educational levels.ial attitudes, teacher training.